Mobile Computing: Trend, Challenges, Trend Topics, Success Factors and Implementation Fields - Erick Fernando; Yulius Denny; Jullend (Universitas Islam Raden Rahmat, Malang, 2023)
This paper aims to explore the development of mobile computing in knowing trends, challenges, trending topics, success factors, and what fields apply to mobile computing. This study uses a systematic literature review (SLR) methodology consisting of several stages: search strategy, literature criteria, data extraction and monitoring, and data synthesis. The analysis results describing the research findings show that from the reviewed articles, it can be concluded that Mobile Computing is implemented to support and play an important role in community and organizational activities in all disciplines. Mobile computing has a very important role in the ease of use of device applications. The research results can also describe the evolution of mobile computing so that it can be studied in more depth.